PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA PADA PERAWAT RS JIWA TAMPAN PEKANBARU - Suci Rahma Dona; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research was conducted at the RS Jiwa Tampan Pekanbaru, which is located on Jalan HR Soebrantas KM 12.5 Pekanbaru. The purpose of the study was to determine and analyze the effect of work motivation and work environment on job satisfaction partially and simultaneously. The research method used is descriptive quantitative analysis obtained from the results of questionnaires distributed to 58 respondents at the Tampan Psychiatric Hospital Pekanbaru, which is then processed with the SPSS program by conducting validity tests, reliability tests, simple linear regression analysis, multiple linear analysis, analysis of determination (R2) and test the hypothesis by testing t (partial) and F (simultaneous). The tests carried out showed that work motivation had a positive and significant effect on job satisfaction, the work environment had a positive and significant effect on job satisfaction, then work motivation and work environment had a positive and significant effect on job satisfaction at the RS Jiwa Tampan Pekanbaru. Keywords: Work Motivation, Work Environment, Job Satisfaction